2011
DOI: 10.1002/mds.23481
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐operative evaluations for DBS in dystonia

Abstract: In common clinical practice, these outcome measures can be administered in an open-label fashion because double blind assessment is only required for ascertaining new treatment indications or research purposes. The same measures are to be used postoperatively to revaluate outcome after DBS. Brain MRI is required to confirm diagnosis and assess structural abnormalities. Other imaging techniques, particularly functional imaging, are used for research purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 108 publications
(208 reference statements)
0
11
0
3
Order By: Relevance
“…30 However, their pathophysiology is complex and not fully understood. 31 Therefore, it is hoped that a reliable, valid, and sensitive clinical measurement of dystonia and choreoathetosis may result in the recognition of dyskinesia patterns that can be related to the observed brain lesions, and subsequently may enhance our insight into the pathophysiology of CP in the long term. Such a tool should also help in the evaluation of existing and emerging treatments for children with CP.…”
Section: Discussionmentioning
confidence: 99%
“…30 However, their pathophysiology is complex and not fully understood. 31 Therefore, it is hoped that a reliable, valid, and sensitive clinical measurement of dystonia and choreoathetosis may result in the recognition of dyskinesia patterns that can be related to the observed brain lesions, and subsequently may enhance our insight into the pathophysiology of CP in the long term. Such a tool should also help in the evaluation of existing and emerging treatments for children with CP.…”
Section: Discussionmentioning
confidence: 99%
“…Several exhaustive reviews have been published already for the treatment of dystonia with DBS (Speelman et al 2010; Bronte-Stewart et al 2011; Andrews et al 2010; Mills et al 2014; Vidailhet et al 2012; Thobois et al 2011; Holloway et al 2006; Isaias et al 2011; Isaias et al 2008; Fox and Alterman 2015), or the genetics of dystonia (Balint and Bhatia 2015; Lohmann and Klein 2013; Moghimi et al 2013; LeDoux 2012). The reader is directed to these prior reviews for more details.…”
Section: Methodsmentioning
confidence: 99%
“…Although some studies have found no apparent influence of TOR1A mutations on DBS outcomes, the weight of the evidence suggests that those with mutations respond better than those with undetermined genetic causes (Speelman et al 2010; Bronte-Stewart et al 2011; Andrews et al 2010; Mills et al 2014; Vidailhet et al 2012; Thobois et al 2011; Holloway et al 2006; Isaias et al 2011; Isaias et al 2008; Fox and Alterman 2015). The differences in the conclusions across various studies of TOR1A mutations are likely to reflect relatively small numbers of mutation-positive cases evaluated, and heterogeneity among the mutation-negative cases to which they were compared.…”
Section: Are Genetic Factors Relevant?mentioning
confidence: 99%
See 2 more Smart Citations